2022
DOI: 10.1038/s41598-022-05992-4
|View full text |Cite
|
Sign up to set email alerts
|

3D pCASL-perfusion in preoperative assessment of brain gliomas in large cohort of patients

Abstract: The aim of the study was to evaluate the role of pseudocontinuous arterial spin labeling perfusion (pCASL-perfusion) in preoperative assessment of cerebral glioma grades. The study group consisted of 253 patients, aged 7–78 years with supratentorial gliomas (65 low-grade gliomas (LGG), 188 high-grade gliomas (HGG)). We used 3D pCASL-perfusion for each patient in order to calculate the tumor blood flow (TBF). We obtained maximal tumor blood flow (maxTBF) in small regions of interest (30 ± 10 mm2) and then norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
5
0
1
Order By: Relevance
“…Meta-analysis studies indicated the usefulness of ASL imaging for grading gliomas [ 14 , 15 ]. Batalov et al [ 20 ] analyzed 253 patients with gliomas who underwent ASL imaging with a PLD of 1525 ms. They demonstrated higher tumor blood flow in high-grade gliomas than in low-grade gliomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meta-analysis studies indicated the usefulness of ASL imaging for grading gliomas [ 14 , 15 ]. Batalov et al [ 20 ] analyzed 253 patients with gliomas who underwent ASL imaging with a PLD of 1525 ms. They demonstrated higher tumor blood flow in high-grade gliomas than in low-grade gliomas.…”
Section: Discussionmentioning
confidence: 99%
“…The PLD should be selected based on the balance between arrival into the tissues and preservation of magnetic labeling. The PLD values described in the previous studies, including the brain tumor studies mentioned above [ 17 , 20 , 21 ], were in the range of 1.5 s to 2 s. A consensus statement recommended 2000 ms for adult clinical patients, considering possible prolongation of the ATT under pathological conditions [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study we focused on the the predictive value of maximum rather than mean TBF, as we have previously showed that maximum TBF is more informativa for glioma diagnosis than mean TBF [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…The latter method seems to be balanced in quality and clinical applicability. There are some positive results concerning ASL in glioma grading [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Elevation of cerebral blood flow (CBF) on CT-and MR-perfusion images is a consequence of tumor-induced neoangiogenesis. Previously, pseudo-continuous arterial spin labeling (pCASL) showed the capability to differentiate high-and low-grade gliomas [9,10]. Perfusion methods were used to study peritumoral edema [11] as well as being successfully employed to differentiate glioblastomas and metastases or glioblastomas and lymphomas [12][13][14].…”
Section: Introductionmentioning
confidence: 99%